Mechanisms and size effects of small to large strain polymerdeformation at the molecular scale - Reilly, Roseanne (Trinity College (Dublin, Ireland). School of Physics, 2013)
A core section of mechanics of materials is to understand the relationship of the mechanics to the nanoscale structure. This has been looked at in metals, ceramics, but in polymers has been virtually untouched. While micron scale polymer physics has been probed, real size effects and changes in polymer behaviour have not. This thesis attempts to remedy this by using diamond flat punch nanoindentation to probe mechanical size effects in polymer materials, from large to small strain. Additionally these findings regarding size effects in polymers are then utilised to investigate the effect of phase separation on the mechanical properties of ultra-thin block copolymers. Block copolymers are a highly technologically relevant material that is currently been investigated for use in the semiconductor industry, meaning the mechanical properties of these ultra thin phase separated films is also technologically relevant. From a size effect point of view, phase separation also effectively adds in an additional length scale into the ultra-thin film case, with the polymers now separated into domains of individual polymers separated by polymer-polymer interfaces.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin